Unravelling the basic concepts and intents of misbehavior in post-truth society - Hrčková, Andrea; Srba, Ivan; Móro, Róbert; Blaho, Radoslav; Šimko, Jakub; Návrat, Pavol; Bieliková, Mária (Bibliotecas. Anales de investigación, 2021)
Objective: To explore the definitions and connections between the terms misinformation, disinformation, fake news, rumors, hoaxes, propaganda and related forms of misbehavior in the online environment. Another objective is to infer the intent of the authors, where relevant. Design/Methodology/Approach: A conceptual analysis of three hundred fifty articles or monographies from all types of disciplines with a priority of the articles focused on terminological analysis was being utilized. A conceptual map of the terminology that is relevant to the post-truth era was created. In the case of the lack of agreement, the etymology of the terms, utilizing dictionaries, terminological databases and encyclopedias, was favored. Results/Discussion: The approach made possible to delimit the borders between the core terms of posttruth society and to classify them according to the intents of the authors: power (influence), money, fun, sexual harassment, hate/discord, ignorance, passion and socialization. These features were identified to be able to differentiate the concepts: falsity (misleadingness, deceptiveness, lack of verification), accuracy, completeness, currency, medium, intent and analyzable unit. The conceptual map, summarizing and visualizing our findings is attached in the article. Conclusions: We argued that disinformation and misinformation are different terms with different authors and intents in the online environment. Likewise, fake news was delimitated as species of disinformation, which is limited by the medium and financial intent. The intent of hoaxers is rather the amusement of the authors or to spread discord between different groups of society. The intent and analyzable units as statement, claim, article, message, event, story and narrative that were identified in the literature, are crucial for the understanding and communication between social (human) scientists and computer scientists in order to better detect and mitigate various types of false information. Originality/Value: The study provides a theoretical background for detecting, analyzing and mitigating false information and misbehavior.